Global, regional, and national burden of age-related macular degeneration, 1990–2019: an age-period-cohort analysis based on the Global Burden of Disease 2019 Study - Huang, Yufan; Tang, Tong; Wang, Dongyue; Gao, Yunxia; Zhang, Ming (Frontiers in Public Health, 2024)
Objectives: This study aimed to explore the burden of disease and disparities in agerelated macular degeneration (AMD) at the global, regional, and national levels from 1990-2019 using data from the Global Burden of Disease (GBD) 2019 study, with a particular focus on associations with age, period, and cohort.We derived disability-adjusted life years (DALYs) and age-standardized rates of AMD from the GBD 2019. We used an age-period-cohort (APC) model to estimate the overall annual percentage changes in DALYs (net drifts), the annual percentage changes in different age groups (local drifts), the longitudinal age profiles (longitudinal age-specific rates), and the relative risks of period and cohort (period and cohort effects) between 1990 and 2019. Further analysis was conducted by country, region, gender and sociodemographic index (SDI).Results: Globally, the number of DALYs increased from 296771.9321 (95% uncertainty interval [UI], 205462.8041-418699.8184) in 1990 to 564055.0967 (95% UI, 392930.6967-789194.6407) in 2019 (59.7% were female), while the agestandardized DALYs rates decreased from 8.29 per 100,000 (95% UI, 5.8-11.58/100,000) to 7.05 per 100,000 (95% UI, 4.92-9.84/100,000). With increasing age, the burden of AMD increased, and the DALYs rates in female was greater than that in male in all age groups. The burden of disease varied across SDI regions and countries.The top three countries in terms of the number of DALYs were China, India and Italy, accounting for 45% of the global total.The burden of AMD varied according to SDI, country, and sex from 1990 to 2019. Due to global population growth and aging, AMD will continue to be a major public health problem in the future, and relevant health policies need to be continuously improved and optimized.